Comparative study of tapered versus conventional cylindrical balloon for stent implantation in stenotic tapered artery. Issue 7 (1st March 2020) - Shen, Xiang; Jiang, Jiabao; Zhu, Hongfei; Lu, Kaikai; Dong, Pengfei; Gu, Linxia
Abstract: The natural tapering of coronary arteries often creates a dilemma for optimal balloon sizing during stenting. The influence of different balloon types, namely, a tapered balloon and a conventional cylindrical balloon, on the mechanical performance of the stent as well as arterial mechanics was investigated via the finite element method. Stent free‐expansion and stent deployment in a stenotic tapered artery were investigated numerically. The biomechanical behavior of the two balloon types was compared in terms of stent foreshortening, stent deformation, stent stress distribution, and arterial wall stress distribution. Results indicate that balloon types affect the transient behavior of the stent and the arterial mechanics. Specifically, a tapered balloon could maintain the natural tapering of the coronary artery after stent expansion. In contrast to a cylindrical balloon, tapered balloon also mitigated the foreshortening of the stent (7.69%) as well as the stress concentration in the stent and artery (8.61% and 4.17%, respectively). Hence, tapered balloons should be used in tapered arteries as they may result in low risk of artery injury. This study might provide insights for improved balloon choice and presurgical planning.